The Political Communication Style of Gibran Toward First-Time Generation Z Voters on Social Media: A Framing Analysis of Diction Aligned with Youth Preferences - Ade Rachmat Yudiyanto; Hasrat Efendi Samosir; Katimin (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This research aims to analyze Gibran Rakabuming Raka's political communication style to Generation Z first-time voters on social media with a framing analysis approach. As a young politician, Gibran utilizes platforms such as TikTok and Instagram to form a more casual, familiar, and relatable political image for young people. Through the use of popular diction such as "bro," "santuy," and "gaskeun," Gibran manages to create the impression of a figure close to young people, while still focusing on relevant political issues. The results showed that visual framing strategies and slang proved effective in attracting Generation Z's attention, but also had the risk of reducing politicians' credibility in the eyes of other audiences. In addition, the use of political gimmicks based on humor and popular culture further strengthens the appeal of Gibran's content on social media, as evidenced by the increase in the number of followers and audience engagement during the campaign period. Therefore, Gibran maintains a balance between casual style and data-driven messaging to remain relevant and credible in the eyes of all voter segments.